Development of Canva-Based Economics E-Module on Cooperative Materials for Class X Social Sciences at SMAN 1 Cerenti - Fitriani, Fitriani; Putri Mayang Sari, (Perspektif Pendidikan dan Keguruan, 2022)
This study aims to produce a product in the form of e-modules that can be used by students in learning. Research and development of economic lesson modules with cooperative materials use the Research and Development (R&D) which include: 1) Potential and problems. 2) Gathering information. 3) Product design. 4) Design validation. 5) Design improvements. 6) Product trial. 7) Product revision. 8) Usage trial. 9) Product revision. 10) Mass production. The research subjects (Economics Educator at SMAN 1 Cerenti), media experts (Lecturer of Accounting Education at Islamic University of Riau), learning practitioners (Economics Educator at SMAN 1 Cerenti), and students in Class X IPS 3 SMAN 1 Cerenti. The results of this study are the availability of teaching materials in the form of electronic modules that have been valid and have also gone through trials from the validation and feasibility tests. Based on the results of validation by material experts the results were 92.7% in the very appropriate category, validation by the first media experts the results were 92.5% in the very feasible category, validation by the second media experts received 93.6% results in the very feasible category, and the validation of the students got the results of 97.4% with very interesting category. From these results, it can be concluded that the e-module product for economic lessons on cooperative materials is feasible to be used in the learning process.